2005
DOI: 10.1139/b05-112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of fringed brome (Bromus ciliatus) as determined by amplified fragment length polymorphism

Abstract: Abstract:Fringed brome (Bromus ciliatus L.) is found in native stands throughout a large area of North America. Little is known about the genetic diversity of this species. The amplified fragment length polymorphism (AFLP) technique was applied to assess the genetic diversity of 16 fringed brome populations sampled in Canada from the provinces of Alberta, British Columbia, Quebec, and Saskatchewan. Four AFLP primer pairs were employed to screen 82 samples with four to six samples per population and 83 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These results are in general agreement with those findings reported in similar studies of other native grass species using amplified fragment length polymorphism (AFLP) markers (e.g., see [50,51]) and other markers (e.g., [52]). An interesting finding is the genetic distinctness of the accessions collected from Nevada and Wyoming, as these plants were collected from the middle range of the species distribution [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in general agreement with those findings reported in similar studies of other native grass species using amplified fragment length polymorphism (AFLP) markers (e.g., see [50,51]) and other markers (e.g., [52]). An interesting finding is the genetic distinctness of the accessions collected from Nevada and Wyoming, as these plants were collected from the middle range of the species distribution [19].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is technically possible to sample genome-wide genetic variability in plants with complex genomes through GBS, even though SNP calling from sequences of a complex, polyploid genome is confounded by the presence of homeologs [54], orthologs, and paralogs [55]. Thousands of SNP markers would be more informative for plant genetic diversity analysis with higher resolution than the several hundreds of AFLP markers normally screened in previous studies [50,51,56,57]. More importantly, the total laboratory and sequencing cost for generating these genomic data on this set of studied samples was roughly $12,000, indicating the feasibility of a wider application of GBS to characterize native grass species.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the sainfoin diversity studies revealed higher level of within-population genetic diversity than among the populations (Table 3). A high level of within-population genetic diversity was also reported for perennial, outcrossing grasses (Fu et al 2005;Biligetu et al 2013). In addition, Demdoum et al (2012) found that the genetic diversity of sainfoin accessions were associated with their geographic locations, with British accessions being separate from other European accessions.…”
Section: Genetic Diversity and Cultivar Developmentmentioning
confidence: 85%
“…Molecular assessments of diversity in native species enhanced the understanding of diversity and can assist in conservation activities. A molecular research program on native Canadian grass species in association with PGRC has existed since 2002 in collaboration with other scientists in AAFC, National Parks, Environment Canada, the University of Saskatchewan, and Ducks Unlimited to conduct 11 research projects on genetic diversity of more than 14 native grass species (Fu et al 2005a;Fu and Thompson 2006;Liu et al 2013;Biligetu et al 2013). Observations of diversity changes over time and space are helpful to make conservation decisions for such plant material (Ferdinandez et al 2005;Fu et al 2005b;Qiu et al 2009).…”
Section: General Assessments Regarding the Conservation And Utilizatimentioning
confidence: 99%